AB1078 Colchicine Use and Risk of Myocardial Infarction among Gout Patients - A General Population Study. (10th June 2014) - Dubreuil, M.; Peloquin, C.; Zhang, Y.; Neogi, T.; Choi, H.K.
Abstract : Background: A recent randomized trial demonstrated a 77% reduced risk of myocardial infarction (MI) among adults with known coronary artery disease treated with long-term low dose colchicine. 1 Whether colchicine reduces the risk of incident MI in gout patients is unknown. Objectives: We examined the association of colchicine use and incident MI among gout patients using data from a general population database (The Health Improvement Network [THIN]). Methods: Included were adults aged 18-89 years who had been enrolled in THIN ≥2 years and had no history of MI. We identified persons who developed gout from 2000-2012, and identified MI cases. In a nested case-control analysis, we matched each gout patient with MI, to 5 gout patients without MI based on age and sex. Colchicine use was categorized as current (prescription within 30 days of index date), recent (31-179 days), past (≥180 days) or never. We conducted a conditional logistic regression model to adjust for potential confounders of MI. We also examined the number of colchicine prescriptions issued in the year prior to the index date in a case-control analysis. Results: Among 55, 509 persons with incident gout, there were 974 cases of MI, matched to 4762 controls. The adjusted ORs for current, recent and past colchicine use (relative to non-use) were 0.96, 1.49, and 1.12 respectively. The adjusted ORs for 1, 2, 3-5, and >6 prescriptions were 1.31 (95% CI 0.97-1.78), 1.50 (0.88-2.55), 1.35 (0.72-2.55) and 0.62 (0.18-2.10) respectively. Conclusions: In this large observational general population study, colchicine use was not associated with a reduced risk of MI among persons with gout. However, colchicine use in this population was generally sporadic (likely for gout flares), rather than continuous. We cannot rule out the potential for confounding by indication. Future studies should identify a larger sample of continuous colchicine users to clarify its potential cardioprotective role in gout. References: Nidorf SM, Eikelboom JW, Budgeon CA, Thompson PL. Low-dose colchicine for secondary prevention of cardiovascular disease. J Am Coll Cardiol. 2013;61(4):404-10. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1664